Spinning a yarn from the wild - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Most of the world's silk is produced in Asia and the Far East with a few countries in Africa developing a small industry using introduced Asian silk moths. But Africa has it's own wild silk moths, although up until now, the cocoons of these wild...